Market volatility on the balance of payments in ASEAN countries - Andini, Nova Riza Ayu (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
This research aims to determine the effect of volatility on the stock market proxied by stock indices and financial markets proxied by exchange rates on the balance of payments proxied by direct investment (FDI) in ASEAN member countries for the period 2013 to 2022. The balance of payments is a systematic record of economic transactions involving one country with another country in a certain period of time, therefore the balance of payments can be influenced by various components, one of which is the market. This research is important because the results of previous research are inconsistent and over time many economic phenomena occur that will affect a country's balance of payments. The novelty of this study lies in its particular focus on the effect of market turmoil on the balance of payments in ASEAN countries. This study used quantitative methods using secondary data. This research uses panel data analysis techniques with a Fixed Effect Model (FEM) approach. The results of this study show that partially the stock index has a significant positive effect and the exchange rate has a significant negative effect on the balance of payments. This research can provide important insights for business decision makers, governments, and international institutions to understand and respond to rapid economic developments in ASEAN.